“Time to Be Young?” – A Qualitative Study Exploring the Impact of Attending a Course for Young Carers Who Have a Parent with Dementia - Haaland-Johansen C; Haugen I; Rokstad AMM (Patient Related Outcome Measures)
Celine Haaland-Johansen,1 Ingebjørg Haugen,2 Anne Marie Mork Rokstad1,3 1Norwegian National Centre for Ageing and Health, Vestfold Hospital Trust, Tønsberg, Norway; 2Faculty of Health Studies, VID Specialized University, Oslo, Norway; 3Faculty of Health Sciences and Social Care, Molde University College, Molde, NorwayCorrespondence: Anne Marie Mork Rokstad, Norwegian National Centre for Ageing and Health, Vestfold Hospital Trust, Postboks 2136, Tønsberg, 3103, Norway, Email anne.m.m.rokstad@himolde.noPurpose: Being a young carer of a parent with dementia can be challenging, with many carers undertaking various practical and caring tasks. The weekend course Time to be young? gathers young carers, aiming to support them to cope with their challenges in everyday life. The aim of this study was to explore their role as a caregiver and the experienced impact of the course on their strategies of coping in their everyday life.Participants and Methods: The study had a qualitative descriptive design inspired by Lindseth and Norberg’s phenomenological hermeneutical method, using individual semi-structured interviews for data collection. The participants were recruited from former participants of the course Time to be young?, and the final sample included eight participants.Results: Through the analysis, four main themes were identified: 1) Help to accept the situation, 2) A sense of community, 3) The need for information and 4) The need to live one’s own life. The study found that attendance at Time to be young? for young adults having a parent with dementia affected their coping strategies in their situation as a young care.Conclusion: The study demonstrated the importance of courses like Time to be young?, and need for a meeting place, tailored information about dementia, and an opportunity to share and reflect upon their experiences as a young carer.Keywords: dementia, young carers, young adults, course, information